Thrombosis-related characteristics of pregnant women with antithrombin deficiency, protein C deficiency and protein S deficiency in Japan - Takao Kobayashi; Kazuko Sugiura; Toshiyuki Ojima; Mariko Serizawa; Kyuya Hirai; Eriko Morishita (Thrombosis Journal, 2024)
Abstract Background  We previously conducted a primary survey of pregnant women with hereditary thrombophilia based on national surveillance in Japan, but did not examine their thrombosis-related characteristics. Antithrombin (AT) deficiency, protein C (PC) deficiency and protein S (PS) deficiency are the major types of hereditary thrombophilia in Japan. Methods We examined their detailed information related to thrombosis, and evaluated peripartum outcomes in comparison with control data obtained from the Japan Society of Obstetrics and Gynecology. Results Definite or probable AT deficiency, PC deficiency and PS deficiency were observed in 80, 50, and 317 pregnancies, respectively, from 2014 to 2018 in Japan, with prevalence rates among total deliveries of 0.011%, 0.007%, 0.044%. The number of pregnancies with AT, PC and PS deficiency might have been as many as 27, 17 and 108 every year if complete answers had been provided. In the peripartum period of current pregnancies, 27.5% of women with AT deficiency, 28.0% with PC deficiency and 13.2% with PS deficiency developed thrombosis (p < 0.001 vs. control). Pregnant women with AT and PC deficiency were more susceptible to thrombosis than those with PS deficiency (P < 0.01). Of the thromboses, 92.3% occurred during pregnancy, 62.8% at less than 15 gestational weeks. The earliest onset of thrombosis was 5 gestational weeks. Prophylactic anticoagulation significantly prevented the onset of both antepartum and postpartum thrombosis (p < 0.0001). The rate of recurrent pregnancy loss in women with low PC or PS activities was significantly higher than in controls (p < 0.0001); however, it is unknown whether recurrent pregnancy loss is related to hereditary PS deficiency. There seem to have been few serious maternal or fetal/neonatal complications due to placental insufficiency related to a hypercoagulable state other than growth restriction. Conclusions This survey revealed the thrombosis-related characteristics of pregnant women with hereditary thrombophilia in Japan. We suggest prophylactic anticoagulation to prevent maternal or fetal/neonatal complications.